Approximation of classes of periodic functions of several variables with given majorant of mixed moduli of continuity - Fedunyk-Yaremchuk, O.V.; Hembars'ka, S.B.; Solich, K.V. (Carpathian Mathematical Publications, 2023)
We obtain the exact-order estimates of approximation of the Nikol'skii-Besov-type classes B^Ω_∞,θ of periodic functions of several variables with a given function Ω(t) of a special form by using linear operators satisfying certain conditions. The approximation error is estimated in the metric of the space L_∞. The obtained estimates of the considered approximation characteristic, in addition to independent interest, can be used to establish the lower bounds of the orthowidths of the corresponding functional classes.